Sigillum Leonis - Книш, Я. (Княжа доба: історія і культура, 2010)
Аналізується опублікована К. Болсуновським латиномовна свинцева печатка, на яку мало звертали уваги науковці. Висловлено думку, що
вона належала князеві Леву Юрійовичу (1308–1323) і використовувалася для внутрішнього вжитку. Дослідник вважає, що двозуб зображений
на печатці, був “зубом князя Лева”. The article examines the leaden seal which was published by
K. Bolsunovkyj and which was largely neglected in the scholarship. Tha article
contends that the seal belonged to Prince Lev Yuriovych (1308–1323) and was
used for internal affairs. The analysis suggests that the double tooth depicted
on the seal was “a tooth of Prince Lev”.